Evaluation on the Effect of Inhibitor Ratio to the Wax Deposition of Local Malaysian Crude - Norida, Ridzuan; Zulkefli, Yaacob; Fatmawati, Adam (2014)
It is important to understand the fundamental nature of petroleum wax formation since this problem is still a challenging issue in the crude oils industry. The application of a wax inhibitor was introduced in this study to reduce the wax. Poly (ethylene-co-vinyl acetate) (EVA) and diethanolmines (DEA) with different ratios were used to evaluate their performance as an inhibitor using cold finger equipment. A total of 10ml of the inhibitor with different ratio was injected into the crude sample where the temperature of cold finger and water bath were setting at 10ºC and 50ºC respectively. The study found that Percent Inhibition Efficiency (PIE) is increased when the amount of EVA in DEA is increased. The use of EVA alone has successfully show 23.1% of wax to the PIE compare to other ratios. The GC-FID analysis found that the C28H (octacosane) wax solid deposit reduced almost 90% if pure EVA was used. This study also concludes that by introducing different 58 ratio between two chemical inhibitors does not give significant effect to the wax solid inhibition formation. Therefore, it highly recommended to used pure EVA as single wax inhibitor to control wax solid deposition.